2023
DOI: 10.1002/adhm.202301729
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Nerve Conduit Made of a Self‐Powered Microneedle Patch for Sciatic Nerve Repair

Abstract: Peripheral nerve defects, particularly those of a larger size, pose a significant challenge in clinical practice due to their limited regenerative capacity. To tackle this challenge, an advanced self‐powered enzyme‐linked microneedle (MN) nerve conduit is designed and fabricated. This innovative conduit is composed of anodic and cathodic MN arrays, which contain glucose oxidase (GOx) and horseradish peroxidase (HRP) encapsulated in ZIF‐8 nanoparticles, respectively. Through an enzymatic cascade reaction, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Following the methodology outlined by Zhang and Ma et al, scratch wound healing assays were conducted with SCs to explore the dual effect of conductive/piezoelectric properties on nerve cell migration. , Briefly, presterilized PCL, PG, and PZG were cocultured with SCs (8 × 10 4 ) in 6-well plates. When the cells reached 100% confluence, a cell-free area was marked with a pipette tip, and the cells were cultured in a serum-free medium to eliminate serum effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the methodology outlined by Zhang and Ma et al, scratch wound healing assays were conducted with SCs to explore the dual effect of conductive/piezoelectric properties on nerve cell migration. , Briefly, presterilized PCL, PG, and PZG were cocultured with SCs (8 × 10 4 ) in 6-well plates. When the cells reached 100% confluence, a cell-free area was marked with a pipette tip, and the cells were cultured in a serum-free medium to eliminate serum effects.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, there is a growing interest in mimicking the structure of sea cucumbers. Microneedles (MNs) are arrays of microscale needles, ranging from 25 to 2000 μm in length, and they are utilized in medicine, skincare, and drug delivery due to their minimal invasiveness, safety, and painlessness. In the realm of nerve injury repair with MNs, our group and Fang’s group have reported on self-powered MNs and exosome delivery MNs used for PNI repair and spinal cord repair, respectively. , However, there have been no reports on the use of MNs for repairing PNI and synergistic inhibition of muscle atrophy. Structurally, the conical needle tips of MNs resemble the structure of sea cucumbers’ conical verrucous feet, albeit differing in size.…”
Section: Introductionmentioning
confidence: 99%
“…Histological evaluations confirmed that the introduction of ZIF-8 nanoparticles facilitated peripheral nerve regeneration. Recently, a self-powered enzyme-linked MN nerve conduit was fabricated [ 202 ]. Half of these MNs were loaded with ZIF-8 encapsulated with glucose oxidase, and half were loaded with ZIF-8 encapsulated with horseradish peroxidase.…”
Section: Application Of Mofs In Tissue Engineeringmentioning
confidence: 99%
“…The nerve autografts have traditionally been hailed as the "golden standard" within critical peripheral nerve deficits. 1 Nevertheless, the functional recovery from the nerve autografts exceeding the threshold of three centimeters has produced a dismaying outcome. A multitude of scholarly inquiries have explored factors that influence the process of regeneration in large-scale nerve lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The nerve autografts have traditionally been hailed as the “golden standard” within critical peripheral nerve deficits . Nevertheless, the functional recovery from the nerve autografts exceeding the threshold of three centimeters has produced a dismaying outcome.…”
Section: Introductionmentioning
confidence: 99%